Expansion of donor-unrestricted MAIT cells with enhanced cytolytic function suitable for TCR redirection - Tiphaine Parrot; Katie Healy; Caroline Boulouis; Michał J. Sobkowiak; Edwin Leeansyah; Soo Aleman; Antonio Bertoletti; Margaret Sällberg Chen; Johan K. Sandberg (JCI Insight, 2021)
Progress in our understanding of MR1-restricted mucosa-associated invariant T (MAIT) cells has raised interest in harnessing these cells for immunotherapy. The innate-like response characteristics, abundance in the blood, donor-unrestricted nature, and tropism for tissues make MAIT cells suitable candidates for adoptive cell transfer therapies. However, reliable methods and tools to utilize MAIT cells in such approaches are lacking. Here, we established methodology for efficient expansion of human MAIT cells in culture with high purity and yield, while preserving their functional response toward their natural ligand and increasing their cytotoxic potential. The cultured MAIT cells retained their effector memory characteristics without signs of terminal differentiation and expressed a more diverse set of chemokine receptors, potentially widening their already broad tissue tropism. To investigate the potential of MAIT cells in a context outside their main role in controlling bacterial infection, we engineered cultured MAIT cells with a new TCR specificity to mediate effective antiviral HLA class I–restricted effector function. In summary, we developed robust and effective methodology for the expansion of human MAIT cells with enhanced cytolytic capacity and for their engineering with a new specificity. These findings form a basis for the development of MAIT cells as a platform for adoptive immunotherapy.